ADAPTASI DESAIN DAN PENGAWASAN KONSTRUKSI AREA KOMERSIAL PANTAI BANGSAL DAN PANTAI MATAHARI TERBIT: Design Adaptation And Construction Supervision Of Commercial Area At The Bangsal And Matahari Terbit Beach - Putra, Ida Bagus Gede Parama; Putra, Ida Bagus Udayana; Sarassantika, I Putu Ellsa (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
The relocation of Sanur Port has led to a 40% decline in traders’ income, shifts in spatial functions, and the deterioration of infrastructure in the Bangsal Beach and Matahari Terbit Beach areas. This Community Service Program was implemented to address the needs of the main partners, namely BUMDA Galang Kangin Sanur, coastal traders, and the local community, through three key activities: design adaptation, masterplan revision, and construction supervision. The program began with field surveys and interviews involving 32 traders, coastal area mapping, and a Focus Group Discussion (FGD) attended by 26 representatives of BUMDA, the traditional village, and MSME groups. The planning process produced several adaptive design outputs, including the initial construction of four modular kiosks using galvanized steel structures, preparation for the improvement of a 300 meter pedestrian corridor that will be developed further depending on community interest, and the introduction of a porous drainage system to mitigate flooding. Periodic construction supervision was carried out to ensure compliance with technical specifications and material durability within the coastal environment. The outcomes of the program indicate improvements in public space comfort, fairer distribution of trading locations, and the strengthening of Balinese architectural identity through contextual design elements. Overall, this program provides direct benefits to coastal traders, BUMDA Sanur, and traditional community stakeholders, and serves as a model for implementing adaptive architectural approaches in the sustainable development of coastal areas.